PEMBAHARUAN DAN PENATAAN SISTEM PERENCANAAN PEMBANGUNAN PENDIDIKAN DI DAERAH - Arifuddin M Arif (Scolae: Journal of Pedagogy, 2018)
The implementation of education renewal planning in the regions cannot be separated from the elements of innovation adopter and other elements involved and involved in the educational innovation process, such as; dimensions of society, politics and economics. There are indications that there are still misconceptions in the real aspects of education development planning in the regions, it is necessary to develop the concept of rearranging education development planning in the regions based on clear, measurable, and accountable approaches, models, methodologies, instruments and achievement indicators.